Monitoring of Drill System Behavior for Water-Powered in-the-hole (ITH) drilling - Ghosh, Rajib; Schunnesson, Håkan; Gustafson, Anna (Minerals, 2017)
A detailed understanding of the drilling system and the drilling control is required to correctly interpret rock mass conditions based on monitored drilling data. This paper analyses data from hydraulic in-the-hole (ITH) drills used in LKAB’s Malmberget mine in Sweden. Drill parameters, including penetration rate, percussive pressure, feed pressure, and rotation pressure, are monitored in underground production holes. Calculated parameters, penetration rate variability, rotation pressure variability, and fracturing are included in the analysis to improve the opportunity to predict rock mass conditions. Principal component analysis (PCA) is used to address non-linearity and variable interactions. The results show that the data contain pronounced hole length-dependent trends, both linear and step-wise linear, for most parameters. It is also suggested that monitoring can be an efficient way to optimize target values for drill parameters, as demonstrated for feed force. Finally, principal component analysis can be used to transfer a number of drill parameters into single components with a more straightforward geomechanical meaning Validerad; 2017; Nivå 2; 2017-08-15 (andbra)